Korea : Transition to a Knowledge-Based Economy - World Bank (Washington, DC, 2013)
The report reviews the economic transition in Korea, summarizing the challenge of the knowledge revolution, to the country's development strategy, and the analytical, and policy framework for a knowledge-based economy. It explores the needs to increase overall productivity, and areas of relative inefficiency, namely, inadequate conditions for generation of knowledge, and information; insufficient competition, and misallocation of investments. Furthermore, the increasingly global, and interdependent world, requires that Korea become inter-nationalized, and this involves: active participation, and leadership in international forums, particularly those setting rules for the new economy; developing alliances with world-class universities; and, active participation in global knowledge systems, and international telecommunications. Thus, the role of the Korean government will need to be redefined, unleashing the creative power of markets, providing legal and regulatory framework for more competitive markets, and fostering policies conducive to enterprise development, while addressing also, the risks of the "digital divide". The report identifies key areas for the government to move towards a comprehensive approach, where reforms are needed to prod: economic incentive, and institutional regime; education, training, and human resource management; information infrastructure; and, innovation systems.